2014
DOI: 10.1093/hmg/ddu277
|View full text |Cite
|
Sign up to set email alerts
|

Coding variants in TREM2 increase risk for Alzheimer's disease

Abstract: The triggering receptor expressed on myeloid 2 (TREM2) is an immune phagocytic receptor expressed on brain microglia known to trigger phagocytosis and regulate the inflammatory response. Homozygous mutations in TREM2 cause Nasu-Hakola disease, a rare recessive form of dementia. A heterozygous TREM2 variant, p.R47H, was recently shown to increase Alzheimer''s disease (AD) risk. We hypothesized that if TREM2 is truly an AD risk gene, there would be additional rare variants in TREM2 that substantially affect AD r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
250
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(258 citation statements)
references
References 44 publications
7
250
1
Order By: Relevance
“…Firstly, p.R62H TREM2 variant appears to be a risk factor for DLB (P = 0.0024, OR;3.2 [95% CI 1.7-27]). This variant was previously reported in association with AD (Jin et al 2014), and although these findings need replication, these observations further emphasize the overlapping genetic etiology of DLB and AD and endorse the view that TREM2 increases the risk of developing several neurodegenerative diseases (Rayaprolu et al 2013). Second, we show the first association of GRN variants with DLB.…”
Section: Discussionsupporting
confidence: 73%
“…Firstly, p.R62H TREM2 variant appears to be a risk factor for DLB (P = 0.0024, OR;3.2 [95% CI 1.7-27]). This variant was previously reported in association with AD (Jin et al 2014), and although these findings need replication, these observations further emphasize the overlapping genetic etiology of DLB and AD and endorse the view that TREM2 increases the risk of developing several neurodegenerative diseases (Rayaprolu et al 2013). Second, we show the first association of GRN variants with DLB.…”
Section: Discussionsupporting
confidence: 73%
“…The significance of this association was subsequently confirmed in several additional studies and meta-analyses (9,(17)(18)(19). rs75932628 causes an R47H missense mutation in the TREM2 ectodomain.…”
mentioning
confidence: 75%
“…Finally, 14 studies were included in the meta-analysis. 13 studies for rs75932628 [11,12,18,19,21,[27][28][29][30][31][32][33][34], 3 studies for rs104894002 [11,32,35], and 4 studies for rs143332484 [12,28,31,32,35]. The selected study characteristics and allele information are shown in Tables 1 and 2, respectively.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%